Du Pont System Analysis In Measuring Financial Performance In Pt. Source Alfaria Trijaya Tbk (Alfamart) - Jariah, Aenun; Pratiwi, Aliah (Jurnal Ekonomi Balance, 2023)
This research analyzes the financial performance of PT. Sumber Alfaria Trijaya Tbk using Du Pont System Analysis on financial report data from 2012 to 2021. The results of the analysis show that Net Profit Margin (NPM) is below industry standards, while Total Assets Turn Over (TATO) shows good performance with a value of above standard. Return On Investment (ROI) and Equity Multiplier (EM) tend to be below industry standards, while Du Pont's Return On Equity (ROE) shows excellent performance. Statistical tests with SPSS validate these findings, showing that NPM, ROI, and EM are below standard, while Du Pont's TATO and ROE are at a good level. The main conclusion of this research is that PT. Sumber Alfaria Trijaya Tbk has good efficiency in asset use, but needs to improve net profit margins, investment management and equity management to ensure higher profitability. Suggestions for companies include further evaluation of financial variables that require special attention, improving strategies to attract new investors, and implementing measures that can improve overall financial performance. These findings can be a guide for PT. Sumber Alfaria Trijaya Tbk to take the necessary actions to improve its financial performance and maintain its position in the market. Thus, this research provides a contribution to stakeholders and future researchers who are interested in analyzing the financial performance of retail companies such as PT. Source Alfaria Trijaya Tbk.